The front end readout system for the T2K-ND280 detectors - Vacheret, A; Greenwood, S; Noy, M; Raymond, M; Weber, A; IEEE (2007)
The Tokai-to-Kamioka (T2K) long baseline neutrino experiment goal is to measure vμto ve oscillation parameters using near (280 m) and far (295 km) detectors from the beam origin in the J-PARC accelerator in Tokai. The far detector will be Super-Kamiokande. The 280 m near detectors complex (ND280) contain a number of scintillator based sub-detectors and a beam monitor. Approximately 54,000 scintillator bars will be read out by Multi-Pixel Photon Counter devices (MPPC) via wavelength shifting fibres. It will be the first time this novel type of photo-sensor is used on such a large scale. The front end readout system for the MPPC uses Fermilab Trip-t chips mounted on Trip-t Front end Boards (TFB). The TFB design and measured performance in conjunction with MPPC photo-sensors are presented. © 2007 IEEE.